Exploring the relationship between distress rumination, resilience, depression, and self-injurious behaviors among Chinese college athletes infected with COVID-19: a cross-sectional study - Zhao, Xiuhan; Liu, Zongyu; Zhao, Liangyu; Zhang, Liguo (Frontiers in Psychiatry, 2023)
Objectives Distress rumination is a cause of suicidality and self-injurious behavior (SSIB) among individuals. Although previous studies have shown that distress rumination, SSIB, resilience, and depression are significantly related, the interaction mechanism remains unclear. This study aimed to evaluate resilience and depression as mediators of the relationship between distress rumination and SSIB among Chinese college athletes infected with COVID-19. Methods Convenience sampling was used to recruit participants from the National College Football Championship in Guangxi City, China from January to February 2023. Participants completed the Ruminative Responses Scale (RRS), a subscale of the Health-Risk Behavior Inventory (HBI), the Mental Toughness Index (MTI) and the Patient Health Questionnaire (PHQ-9). We used the PROCESS macro for SPSS to determine the mediating effect of resilience and depression between distress rumination and SSIB. Results A total of 350 Chinese college athletes participated in this study and completed the questionnaire survey. 289 (81.7% boys; Mage = 20.31 years, SD = 1.60) of them have been infected with COVID-19. 59.9% (n = 173) participants were from urban areas and 15.6% (n = 45) of participants have engaged in self-injurious behaviors or suicidal ideation. College athletes’ distress rumination was significantly negatively correlated with resilience (r = − 0.28, p < 0.01), and was significantly positively correlated with depression (r = 0.49, p < 0.01) and SSIB (r = − 0.18, p < 0.01). Resilience was significantly negatively correlated with depression (r = − 0.35, p < 0.01) and SSIB (r = − 0.30, p < 0.01). Finally, depression was significantly positively correlated with SSIB (r = − 0.38, p < 0.01). Resilience and depression played a mediating role of the total effects of distress rumination and SSIB, respectively. Meanwhile, the chain mediating effect of resilience and depression was also significant. Conclusion This study found that distress rumination can directly predict SSIB, and indirectly predict SSIB through the mediating effect of resilience and depression, and the chain mediating effect of resilience-depression. Therefore, reducing the degree of distress rumination of college athletes infected by COVID-19 and improving their resilience, as well as reducing their depression may help prevent SSIB.